Executive selection process and job satisfaction: The case of the independent authority for public revenue (IAPR) in Greece - Dimitris Apostolakos; Theodore Metaxas (Administrative Sciences, 2021)
This paper assesses the impact that the degree of acceptance of the selection process, as conducted by the human recourses management (HRM), has upon job satisfaction in the local tax offices (LTOs) in Greece. Furthermore, it examines the effects that various individual and demographic characteristics have on job satisfaction. The research was performed using primary statistical data by distributing and collecting specific questionnaires, which not only recorded the level of job satisfaction but also noted the degree of acceptance of the selection procedure in the IAPR. The collected statistical data were analyzed using the IBM SPSS Statistics 26 Fixpack 1 software program. The results showed an average acceptance value of the selection process of 4.89, indicating a high degree of participant consensus with this process. They also showed that age, work experience, and the acceptance of the selection process have a positive and statistically significant effect, whereas educational level has a negative and statistically significant effect on degree of job satisfaction. The added value of the present paper lies in the fact that this kind of research, conducted in the IAPR in Greece for the very first time, measured both the degree of job satisfaction and the effect that the acceptance of the selection procedure has on this attitude.
Keywords: 350; HRM; IAPR; job satisfaction; organizational behavior; public sector; selection procedure